BEUTEL, Albrecht (Ed.). Luther Handbuch. 2a ed. Tübingen: J. C. B. Mohr, 2010, 537 p. - Schwambach, Claus (Vox Scripturae - Revista Teológica Internacional, 2014)
BEUTEL, Albrecht (Ed.). Luther Handbuch. 2a ed. Tübingen: J. C. B. Mohr, 2010, 537 p.